International Legal Regulation of Labor in the Russian Federation - BELOZEROVA, Olga A.; ALEKSANDROV, Ivan F.; DELTSOVA, Natalia V.; KOT, Marina K.; STARTSEVA, Svetlana V. (Journal of Advanced Research in Law and Economics, 2018)
Russia’s entering the global society and acknowledging the international normative acts to be superior to domestic labor law, strengthening of interaction between international and national law, and provision of citizens’ rights for decent conditions of labor – all this proves topicality of the performed research. The purpose of the work is to determine the value and level of influence of the norms of international law in the labor sphere in the Russian Federation and to analyze correspondence of the Russian labor law to international principles and norms. The methodological basis of the performed research consists of general scientific methods: analysis and synthesis, induction and deduction, systemic and functional approaches, analogy and modeling; rather-legal, formal and logical, and statistical methods. The novelty of the research consists in the fact that the authors study international normative acts, adopted and ratified by Russia, and distinguish the problems of implementation of citizens’ labor rights on the territory of the Russian Federation in the context of international legal acts. Based on the performed scientific analysis, certain conclusions were made, necessary for improvement of the law and law enforcement practice, and the problems that appear due to Russia’s adopting and ratifying international legal acts are determined